Cervicothoracic Arthrodesis: The Best Management for Dropped Head Syndrome, A Case Series - Brandão, Matheus Felipe Henriques; Martins, Thiago Gomes; Farias, Ronald de Lucena; Souza, Giácomo de Freitas; Veras, José Vítor Martins (Arquivos Brasileiros de Neurocirurgia: Brazilian Neurosurgery, 2025)
The authors present two cases of Dropped Head Syndrome (DHS), a condition distinguished by the chin-on-chest deformity due to weakness of the posterior muscle group of the neck. This is a unimodal syndrome and is most common among individuals in their seventh and eighth decade of life, with an average age of around 75 years. DHS is more prevalent in women, with a 3:2 ratio compared with men. Our reports document the disease's natural progression, increasing kyphosis, and resistance to initial conservative treatments. Both patients reported functional limitations, as their ability to walk and eat without assistance was hindered by loss of the horizontal gaze and dysphagia. After these treatment failures, we utilized an arthrodesis approach to target the C2-T6 segments of the cervical-thoracic spine. All previous complaints were resolved, the deformity was reduced, and the patients regained their functional independence. The surgical approach is indeed more efficient, although the combination of both methods yielded even better clinical outcomes. Arthrodesis from C2 to the upper thoracic spine segments is considered the most appropriate surgical technique for maintaining subaxial spine movement. This is due to its excellent rate of correcting deformities, preserving horizontal gaze, and improving or maintaining a neurological state.
Keywords: dropped head syndrome; kyphosis and surgery